Do budgetary institutions mitigate the common pool problem? New empirical evidence for the EU - Jakob de Haan; Richard Jong-A-Pin; Jochen O. Mierau (ETH Zurich, KOF Swiss Economic Institute, 2012)
We analyze how budgetary institutions affect government budget deficits in member states of the European Union during 1984-2003 employing new indicators provided by Hallerberg et al. (2009). Using panel fixed effects models, we examine whether the impact of budgetary institutions on budget deficits is conditioned by political fragmentation (i.e., ideological differences among parties in government) and size fragmentation (i.e., the effective number of parties in government or the number of spending ministers). Our results suggest that strong budgetary institutions, no matter whether they are based on delegation to a strong minister of finance or on fiscal contracts, reduce the deficit bias in case of strong ideological fragmentation. In contrast, the impact of budgetary institutions is not conditioned by size fragmentation.
Keywords: H62; 330; budgetary institutions; fiscal policy; political fragmentation; size fragmentation; Haushaltsdefizit; Finanzpolitik; Politisches System; Systemvergleich; EU-Staaten